Compression Bandaging Improves Mobility following Total Knee Replacement in An Enhanced Recovery Setting. Issue 4 (April 2014) - Cheung, A; Lykostratis, H; Holloway, I
The early functional outcome was assessed in 180 patients undergoing total knee replacement (TKR) using compression bandaging versus standard crepe bandaging. Patients with a compression bandage following TKR were significantly more likely to be discharged with a walking stick (p=0.002) and less likely to be discharged with a rollator frame (p=0.001). These patients demonstrated an improved range of knee flexion and ability to straight leg raise at discharge.